(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2018)
The present work, which constitutes a research advance of the project entitled "Contributions to the Understanding of the History of Livestock Farming in the Savannahs of the Sarare River, Lara State, Venezuela at the beginning of the Republican era;1810-1870", has an interdisciplinary perspective while following the guidelines of Social History or Synthesis and using the Geophysical Approach; seeks to contribute to the understanding of livestock production activities in the Sarare River Savannah area between the beginning and the middle of the 19th century, highlighting their impact on history and local and regional development, as well as their importance as a logistical and material base for the strategic approach and operational execution of the military actions in the Barquisimeto area carried out by the patriot and realistic armies in the War of Independence and the revolutionary and centralist troops during the Federal War in Venezuela.